SAIL : The Corporate Strategy - Subramanian, M.; Vidya, Suresh (Journal of Contemporary Research in Management (JCRM), 2013)
According to F.David, “Strategic or institutional management is the conduct of drafting, implementing and evaluating cross-functional decisions that will enable an organization to achieve its long-term objectives’. Johnson and Scholes present a model in which strategic options are evaluated against three key success criteria namely suitability, feasibility, and acceptability. There is a growing consensus among corporate leaders that taking action on climate change is a responsible business decision. From market shifts to regulatory constraints, climate change poses real risks and opportunities that companies must begin planning for today, or risk losing ground to their more forward-thinking competitors. Prudent steps that are taken now to address climate change can improve a company’s competitive position relative to its peers and earn it a seat at the table to influence climate policy. With more and more action at the state level and increasing scientific clarity, it is time for businesses to craft corporate strategies that address dynamic change. One of the chief reasons for the failure of missions and visions to achieve the desired objective is the naiveté (lack of experience / judgment) of most company managers and executives. The aim of the paper is not only to discuss why strategic plan fails but also to provide a solution to make strategy work for from time to time. The paper aims to build a new model SAIL to make the corporate strategies more effective.